2009
DOI: 10.2116/analsci.25.723
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Gel Extraction of Gold(III), Palladium(II), Platinum(II), and Lead(II) as Thiourea-complexes

Abstract: Anionic surfactant solutions of sodium dodecylbenzenesulfonate (SDBS) and sodium dodecylsulfate (SDS) separate into two phases through cooling of the solution and the addition of salts. Thiourea (TU) reacts with many metals to form cationic complexes of [M(TU)n] m+ ; some of them extract into the SDBS phase. The separation was examined for lead and tin in commercially purchased solders. More than 95% lead was extracted into the SDBS phase, while tin remained in the aqueous phase. An abnormal decrease in extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…11 We also confirmed that thiourea -complexes formed ion-pairs with the anionic surfactant, 12 and that the chloro complexes also formed ion-pairs with the cationic surfactant. [13][14][15] The purpose of the present study was to clarify the properties of the ion-pairs and to propose a new separation method for metal ions.…”
Section: Introductionsupporting
confidence: 59%
“…11 We also confirmed that thiourea -complexes formed ion-pairs with the anionic surfactant, 12 and that the chloro complexes also formed ion-pairs with the cationic surfactant. [13][14][15] The purpose of the present study was to clarify the properties of the ion-pairs and to propose a new separation method for metal ions.…”
Section: Introductionsupporting
confidence: 59%
“…The head groups of surfactant molecule bind metal ions reversibly through complexation, electron attraction and/or charge neutralization [22]. The higher moieties for heavy metal ions may be due to higher binding constant for them on surfactant molecules in the matrix of inorganic precipitate [28].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction methods based on temperature-induced phase separation of aqueous ionic micellar solutions may resemble the CPE method using nonionic surfactants [13]. However, we previously reported that an unexpected decrease in extractability was observed at low metal concentrations for the ion-pair extraction of dodecylsulfate anions (DS -) and cationic metal ammine complexes.…”
Section: Solvent Extraction Research and Development Japan Vol 20mentioning
confidence: 99%